Before you found me : a novel - Beyfuss, Brooke (Sourcebooks Landmark, 2023)
"How far would you go to save a child who isn't even yours? Before You Found Me explores the unlikely bond that develops between two abuse survivors and takes a deep dive into personal sacrifice, morality, and the healing powers of family--both blood and found--from the author of After We Were Stolen. Rowan McNamara doesn't open the door to her new life--she's thrown through it. Following an explosive argument with her abusive fiancé, Rowan runs. With no family except for her estranged sister, Celia, Rowan takes refuge in an idyllic New England town. There, she meets Gabriel, the eleven-year-old son of her neighbor, Lee. Lee is welcoming, friendly, and a little too helpful. But Gabriel is a mystery: withdrawn, often bruised, and only willing to speak to Rowan through his basement window. When she discovers that Lee has kept Gabriel imprisoned for the past three years, Rowan is desperate to save him. Fueled by outrage and empathy, she abducts Gabriel and flees to her childhood home in rural Oklahoma, determined to raise him as her own. Together they battle nightmares, curious stares, and Celia's constant disapproval. But when Lee begins haunting more than their dreams, Rowan and Gabriel realize they stopped pretending to be a family a long time ago. Their bond is just as strong as blood, and they're willing to do anything to protect one another. From Brooke Beyfuss comes a tender, deeply emotional novel exploring trauma and healing, love and family, and the impossible lengths we'll go to protect the ones we love, even at the expense of ourselves"--